Acute effects of high-intensity intermittent training on kinematics and foot strike patterns in endurance runners - Latorre-Román, P. A.; Garcia Pinillos, F.; Bujalance-Moreno, P.; Soto-Hermoso, V. M. (Journal of Sports Sciences, 2017)
The main purpose of this study was to evaluate running kinematic characteristics and foot strike patterns (FSP) during early and late stages of actual and common high-intensity intermittent training (HIIT): 5 × 2000 m with 120-s recovery between runs. Thirteen healthy, elite, highly trained male endurance runners participated in this study. They each had a personal record in the half-marathon of 70 ± 2.24 min, and each had a minimum experience of 4 years of training and competition. Heart rate (HR) and rate of perceived exertion (RPE) were monitored during HIIT. High levels of exhaustion were reached by the athletes during HIIT (HRpeak: 174.30 bpm; RPE: 17.23). There was a significant increase of HRpeak and RPE during HIIT; nevertheless, time for each run remained unchanged. A within-protocol paired t-test (first vs. last run) revealed no significant changes (P = 0.05) in kinematics variables and FSP variables during HIIT. There were no substantial changes on kinematics and FSP characteristics in endurance runners after fatigue induced by a HIIT. Only the minimum ankle alignment showed a significant change. The author suggests that these results might be due to both the high athletic level of participants and their experience in HIIT.